The Trans-Neptunian Solar System 2020
DOI: 10.1016/b978-0-12-816490-7.00003-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the distribution of orbits of distant Trans-Neptunian objects

Abstract: Looking at the orbits of small bodies with large semimajor axes, we are compelled to see patterns. Some of these patterns are noted as strong indicators of new or hidden processes in the outer Solar System, others are substantially generated by observational biases, and still others may be completely overlooked. We can gain insight into the current and past structure of the outer Solar System through a careful examination of these orbit patterns. In this chapter, we discuss the implications of the observed orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Therefore a dedicated TNO survey is more suitable and desired for extensive follow-up observations, as well as characterization of the above biases. For a review on the biases associated with KBO observations, see Kavelaars et al (2020).…”
Section: Dynamical Structure Of the Kuiper Beltmentioning
confidence: 99%
“…Therefore a dedicated TNO survey is more suitable and desired for extensive follow-up observations, as well as characterization of the above biases. For a review on the biases associated with KBO observations, see Kavelaars et al (2020).…”
Section: Dynamical Structure Of the Kuiper Beltmentioning
confidence: 99%
“…Current predictions suggest that the LSST alone could be responsible for a five-fold Completeness for various populations; baseline LSST simulations PHA @H<20.00 PHA @H<22.00 NEO @H<20.00 NEO @H<22.00 MBA @H<18.00 MBA @H<21.00 Trojan @H<16.00 Trojan @H<18.00 TNO @H<6.00 TNO @H<8.00 Figure 1. LSST discovery completeness as a function of time, for various modeled solar system populations (Granvik et al 2018;Grav et al 2011;Petit et al 2011;Kavelaars et al 2009). Cumulative completeness is reported for two different absolute magnitude (H) values; one near the bright end of the population (solid lines) and one near the 50% completeness level (dashed lines).…”
Section: Near-earth Objectsmentioning
confidence: 99%
“…In a recent paper, , we showed that O(20) Earth masses are required for the instability to occur in a primordial scattered disk between ∼ 10 2 − 10 3 AU in the solar system under the orbit-averaged, gravitational influence of the giant planets. The instability can also generate a gap in perihelion at a few hundred AU, as observed in the outer solar system (Kavelaars et al 2020). The saturation timescale for the instability in a 20 Earth mass disk is 660 Myr, far less than the age of the solar system.…”
Section: Introductionmentioning
confidence: 96%